Just mothers: criminal justice, care ethics and 'disabled' offenders. Issue 6 (2nd July 2020) - Rogers, Chrissie
Abstract: Research with prisoners' families is limited in the context of learning difficulties/disabilities and autism. Life-story interviews with mothers reveal an extended period of emotional and practical care labour, as the continuous engagement with their sons' education and experiences of physical and emotional abuse are explored. Prior to their sons' incarceration, mothers spoke of stigma and barriers to support throughout their childrearing, as well as limited or absent preventative/positive care practices. Subsequently, prisons and locked wards seem to feature as a progression. Mothers have experienced abuse, physical and/or emotional, as well as lives that convey accounts of failure of the systems. A care ethics model of disability assists an analysis of the narratives where care-less spaces are identified. Interrelated experiences, merging emotional responses with extended mothering, the external forces of disablism and destructive systems, lead to proposing rehumanisation of care practices within, for example, education and the criminal justice system.